Pseudopregnancy in dairy goats - a case study - Villanueva R., Edgar (2012)
The aim of this study was to determine the presence of hydrometra or pseudopregnancy in 38 dairy goats raised under intensive system. The diagnosis was done using transabdominal ultrasonography at 45 days of natural service. The affected goats were diagnosed as positive when the uterus presented a visible accumulation of fluid and presence of trabeculae in the image. The incidence of a hydrometra was of 5.3%. Both affected animals were successfully treated with commercial prostaglandin (PGF2α), and estruses occurred 4 days after the treatment. One goat got pregnant while the hydrometra recurred in the other goat.